2005
DOI: 10.4049/jimmunol.175.1.517
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Cyclophilins Contribute to the Regulation of Inflammatory Responses

Abstract: The main regulators of leukocyte trafficking during inflammatory responses are chemokines. However, another class of recently identified chemotactic agents is extracellular cyclophilins, the proteins mostly known as receptors for the immunosuppressive drug, cyclosporine A. Cyclophilins can induce leukocyte chemotaxis in vitro and have been detected at elevated levels in inflamed tissues, suggesting that they might contribute to inflammatory responses. We recently identified CD147 as the main signaling receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
219
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(234 citation statements)
references
References 23 publications
(21 reference statements)
9
219
0
2
Order By: Relevance
“…It is known that macrophages express Bsg, and that Bsg could be a ligand for E-selectin. 27,34 We also confirmed that Bsg on THP-1, the human monocytic cell line, bound to E-selectin (data not shown). Consider- ing that E-selectin expression was induced to similar degrees in both genotypes, it is likely that the difference in macrophage infiltration between Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice is due to the presence of Bsg on macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…It is known that macrophages express Bsg, and that Bsg could be a ligand for E-selectin. 27,34 We also confirmed that Bsg on THP-1, the human monocytic cell line, bound to E-selectin (data not shown). Consider- ing that E-selectin expression was induced to similar degrees in both genotypes, it is likely that the difference in macrophage infiltration between Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice is due to the presence of Bsg on macrophages.…”
Section: Discussionsupporting
confidence: 65%
“…AAEL011758 and AAEL013279 are predicted cyclophilins. The involvement of cyclophilins in immune response has been documented in D. melanogaster (Guedes et al, 2005) and mammals (Arora et al, 2005;Barik, 2006) and has been proposed in Xenopus laevis, where a cyclophilin is found in skin secretions (Miele et al, 2003).…”
Section: E Defense Response and Toxicity-mentioning
confidence: 97%
“…For example, CypAeCsA complex can bind and inhibit calcineurin in T-lymphocytes, which blocks the T cell signal transduction to achieve immunosuppression [19]. Although CypA was originally believed to exist solely as an intracellular protein, later studies have revealed that it can be secreted by cells in response to inflammatory stimuli [20]. The clinical importance of Cyps has been implicated in diverse pathological conditions, such as HIV [21], hepatitis B and C viral infection [22], atherosclerosis [23], vascular diseases [24] and Rheumatoid Arthritis pathogenesis [25].…”
Section: Introductionmentioning
confidence: 99%